On approximate solutions of an iterative functional equation - Baron, Karol; Simon, Alice (Annales Mathematicae Silesianae, 1994)
We consider approximate solutions of the functional equation (1) in the class of functions which satisfy on compact sets the condition (2) with an increasing, subadditive, continuous at zero and vanishing at zero function γ: [0,+∞)→[0.+∞).